Ethical criteria for medicinal drug promotion - World Health Organization (Geneva : WHO, 1988)
Elaborates ethical criteria for the promotion of medicinal drugs. The criteria, which are based on a draft prepared by an international group of experts, constitute a frame of reference for judging proper behaviour in drug promotion, whether involving the content of advertisements and package inserts or the sponsorship of scientific symposia and the use of sales representatives. Endorsed by the World Health Assembly in May 1988, the criteria will give manufacturers and distributors, the promotion industry, prescribers, and consumer groups a useful framework for developing measures to ensure that promotional practices involving drugs are in keeping with acceptable ethical standards
Keywords: Ethics, Pharmacy; Pharmacology -- ethics